Teaching Medicine Online During the COVID-19 Pandemic: A Malaysian Perspective (Bangladesh Journal of Medical Science, 2020)
The COVID-19 pandemic affected institution of higher learning as some teaching and learning activities had to halt due to safety of the students and staff. Face to face teaching was stopped, and lecturers had to find other methods of teaching. Online teaching was the only allowed method. The methods were synchronous and asynchronous. Lecturers have had to find innovative ways to practice effective teaching methods. Assessments had to also be done online taking important factors into consideration, following steps given by authorities. This article discusses issues around medical teaching during the COVID-19 pandemicBangladesh Journal of Medical Science Vol.19(0) 2020 p. S 77-S 81